ANTIBACTERIAL ACTIVITY OF ENDEMIC BALLOTA NIGRA SUBSP. ANATOLICA AGAINST SOME HUMAN EYE PATHOGENS FROM TURKEY - Dulger, Gorkem; Dulger, Basaran (Innovare Journal of Life Sciences, 2017)
ABSTRACT Objective: The ethanol extracts obtained from the leaves of Ballota nigra subsp. anatolica P.H. Davis (Lamiaceae) were evaluated for their antibacterial activity against some human eye pathogens. Methods: Hospital isolates of Bacillus cereus, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus capitis, S. aureus, Staphylococcus epidermidis, Moraxella nonliquefaciens, and Propionibacterium acnes were obtained. Antibacterial activity was determined in the extracts using disc diffusion method. Some antibacterial antibiotics were used as a positive reference standard to determine the sensitivity of the isolates. Results: The extracts showed strong antibacterial activity against M. nonliquefaciens and P. acnes, with inhibition zones of 18.2 mm and 19.2 mm, respectively. The extracts also exhibited moderate activity against the other isolates. Conclusion: The results demonstrate that the leaf extract of the plant has significant activity and suggest that it may be useful in the treatment of eye infections. Keywords: Ballota nigra subsp. anatolica, Antibacterial activity, Eye pathogens.